2018
DOI: 10.1007/s11051-018-4407-z
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-conjugated multi-walled carbon nanotubes as a new targeted ultrasound contrast agent for the diagnosis of prostate cancer

Abstract: Early diagnosis is primarily important for the therapeutic and prognostic outcomes of malignancies including prostate cancer (PCa). However, the visuality and veracity of ultrasound imaging for the diagnosis and prognostic prediction of PCa remains poor at present. In this study, we developed a new nanoultrasound contrast agent by modifying multi-walled carbon nanotubes (MWCNTs) with polyethylene glycol (PEG) and anti-PSMA aptamer. The result showed that the modified MWCNTs offered better visuality and veracit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…The in vivo enhancement effect of aptamer-conjugated nanotubes was assessed in the transplanted tumor model by Gu et al, and they found that higher accumulation was found in the tumor, heart, and kidney. 47 The same phenomenon was observed in this study that APT-DTXp/DDP-LPHNs showed the highest accumulation in the tumor and lower in heart and kidney. APT-DTXp/DDP-LPHNs showed better antitumor efficiency than non-decorated DTXp/DDP-LPHNs, which may prove the targeted ability of the aptamer.…”
supporting
confidence: 84%
“…The in vivo enhancement effect of aptamer-conjugated nanotubes was assessed in the transplanted tumor model by Gu et al, and they found that higher accumulation was found in the tumor, heart, and kidney. 47 The same phenomenon was observed in this study that APT-DTXp/DDP-LPHNs showed the highest accumulation in the tumor and lower in heart and kidney. APT-DTXp/DDP-LPHNs showed better antitumor efficiency than non-decorated DTXp/DDP-LPHNs, which may prove the targeted ability of the aptamer.…”
supporting
confidence: 84%
“…As a brief study, Gu and co-workers studied CNTs conjugated with anti-PSMA aptamer and PEG as a nanoultrasound contrast agent ( Figure 4 b) and they found out that the contrast has superior visuality, good distribution and development effect. The conjugated CNT/aptamer was also capable of specific targeting of prostate cancer (PCa) cells due to good cell uptake [ 96 ]. However, CNTs, due to their ability to pass through the blood–brain barrier, are toxic to organs and can induce death at very high dosage but, at low dosage, they can serve as therapeutic drug delivery agents [ 99 ].…”
Section: Nanomaterials Based Aptamer Sensors As Diagnostic Toolmentioning
confidence: 99%
“…( a - i ) Stepwise synthesis of aptasensor based on conjugates of CNTs, polyethylene glycol (PEG) and aptamer, ( a - ii ) the cellular uptake of a CNT-based aptasensor at different concentrations monitored by flow cytometry, ( a - iii ) concentration dependency of the aptasensor toxicity in cells. Adapted from Gu et al [ 96 ] with permission from Springer. ( b ) Experimental setup for the immobilization of peptide aptamer onto the surface of a CNT and the operating set-up of the liquid-dated CNT FET device for CatE detection.…”
Section: Figurementioning
confidence: 99%
“…Their biomedical applications include long‐lasting US imaging, PA imaging, drug delivery, PTT, and electrochemical biosensor systems. [ 71‐74 ] For example, PEGylated MWCNTs modified with prostate‐specific membrane antigen (PSMA)‐targeting aptamer A10‐3.2 were developed as US imaging contrast agents for prostate cancer. The results were promising regarding the diameter, distribution and metabolism of the US contrast agent.…”
Section: Classifications Of Npsmentioning
confidence: 99%
“…The results were promising regarding the diameter, distribution and metabolism of the US contrast agent. [ 71 ]…”
Section: Classifications Of Npsmentioning
confidence: 99%